Waste Segregation Program Evaluation in Improving Domestic Waste Management Effectiveness at PT Pabrik Kertas Tjiwi Kimia Tbk: Evaluasi Program Pemilahan Sampah dalam Meningkatkan Efektivitas Pengelolaan Sampah Domestik Di PT Pabrik Kertas Tjiwi Kimia Tbk - Tiara Salsabilla Prabasari; R. Mohammad Alghaf Dienullah; Sekarsari Wibowo; Abdillah Akmal Karami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Domestic waste management in the industrial sector requires an effective system, one of which begins with waste sorting at source. This applied study aims to evaluate the compliance of the waste sorting program in the paper industry with existing regulations. The method used is descriptive qualitative through field observations, waste inventory data and literature studies, and refers to applicable regulations. The study results indicate that the waste generated consists of organic, inorganic, and residual waste that has been sorted and managed according to its characteristics. Waste utilization is carried out through processing in the RDF (Refuse Derived Fuel) boiler, maggot feed, and internal and external recycling. This program contributes to increasing management efficiency and reducing waste to the Final Processing Site. Optimization is still needed through increasing consistency of sorting and participation of all parties to support sustainable waste management.